Evaluating the potential of Nuig2 metal-organic framework for adsorption of short linear alkanes at low pressure - Borzehandani, Mostafa Yousefzadeh; Abdulmalek, Emilia; Abdul Rahman, Mohd Basyaruddin; Mohammad Latif, Muhammad Alif (Elsevier, 2023)
For the first time, metal-organic framework NUIG2 has been investigated for the adsorption and separation of methane (C1), ethane (C2), propane (C3) and butane (C4) at low pressure. In order to calculate the loading and mobility of the gas molecules inside NUIG2, grand canonical Monte Carlo and molecular dynamics simulations were performed. C2 and C3 had the maximum loading on the framework because of their appropriate molecular size and tightly fitting into the pores. On the other hand, C1 molecules were able to be freely situated in all pores, but C4 molecules were accommodated only into the largest channels. Radial distribution function analysis revealed that methyl and phenyl groups of the framework were the most favorable sites for hydrophobic interaction with the gas molecules. The Henry coefficient indicated that the adsorption affinity of the gas molecules into the NUIG2’s pores was in the order of C1 < C2 < C3 < C4 following molecular size. The diffusion of C1 molecules were significantly fast, while its loading was high in the framework. However, C3 and C4 molecules did not demonstrate any diffusion at any loading. Overall, we have concluded that NUIG2 is desirable for the adsorption of C2 and C3, whereas is beneficial for the selectivity of C4 over C1 molecules. NUIG2 is expected to be a very promising MOF for further study into the adsorption and separation of alternative gases.